"The Significance Of Mineralized Breccia Pipes" - V. D. Perry (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1961)
Mineralized breccia pipes, because of their wide-spread occurrence and close structural relations to some of the world's great ore bodies, are objects of unusual interest for mining engineers and geologists. The literature contains many references to them, but it is questionable whether their genetic significance and economic importance have been sufficiently emphasized. The purpose here is to stress these features, relating them to the field facts, for the particular benefit of younger generations of geologists who, confronted with and sometimes confused by the growing flood of geochemical, geophysical, and other specialized research approaches, may be reassured that mappable field relations remain a foremost guide to a better understanding of ore deposits. A mineralized breccia pipe is a pre-mineral, breccia structure which has controlled the circulation and deposition of subsequently introduced mineralization. It is composed of relatively rotated angular or rounded rock fragments, set in a mineralized matrix. A pipe in plan outline may be circular, oval or approach polygonal form, with a steep to vertical axis proportionately much greater than its horizontal dimensions. The pipe is a steeply plunging, chimney-like mass of brecciated rock cemented with later minerals.